AI-Generated Green Brand Storytelling with Narrative Rhetoric and Its Impact on Immersion, Brand Trust, and Brand Loyalty - Dina Mardhatilah; Elisabet Dita Septiari (Yayasan Darussalam Bengkulu, 2026)
Background: Rising consumer skepticism toward palm oil-based products due to desirability concerns has prompted companies to adopt more persuasive communication strategies. However, empirical research examining the effectiveness of AI-generated green brand storytelling integrated with narrative rhetoric is limited. This study aims to investigate the impact of narrative rhetoric storytelling on immersion, brand trust, and brand loyalty. Method: This study uses a quantitative method where data were collected from 350 respondents using purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), supplemented by an independent sample t-test. Results: The findings indicate that storytelling incorporating elements of narrative rhetoric has a significantly stronger effect on brand loyalty compared to non-narrative storytelling. Furthermore, anthropomorphism, reversal, and symbolism significantly increase consumer immersion, with symbolism showing the strongest effect. Immersion was found to significantly influence brand trust, which in turn was the most significant predictor of brand loyalty. Conclusion: The conclusion highlight the sequential mechanisms by which narrative rhetorical elements increase engagement, which strengthens trust and ultimately drives loyalty. This study extends narrative rhetorical theory by demonstrating its role in sustainability communication and provides empirical evidence that persuasive storytelling can effectively reduce consumer skepticism and strengthen long-term brand relationships in the context of palm oil-based products